Process proposal to creating and evaluating value for the customer - Miguel, Lilian Aparecida P; Marcondes, Reynaldo Cavalheiro; Caldeira, Adilson (Práticas em Contabilidade e Gestão, 2023)
This article proposes a set of indicators to measure the value creation for the client to offer companies a working guide. Although in a more academic format, a practical application of these indicators is proposed, based on a process of value creation, where the client, the consumer, and the organizations’ stakeholders are contemplated. This work was elaborated based on the many aspects defended in relation to the concept of value creation, having as focus and premise the market aspect, involving all the organization’s stakeholders, main actors, and coadjutants in creating organizational value. Despite the many papers on the subject, this work is justified by the apparent pragmatic gap in Brazil. Therefore, it seems appropriate to offer a proposal for a value creation process, which will capture the main approaches that involve such a theme, as well as point out a set of indicators to measure the created value.